First fossil record of peccaries (Artiodactyla, Tayassuidae) from the Upper Miocene (Hh3: Late Hemphillian) of Costa Rica, Central America - Valerio, Ana L. (2020)
For the first time is recorded the Tayassuidae Family as fossil at the Cenozoic of Costa Rica. Two peccary species, Prosthennops serus (Cope, 1878) and Protherohyus brachydontus Mooser y Dalquest (1980) are described from the San Gerardo de Limoncito fossiliferous locality at Southern Costa Rica. The sympatric distribution of both species is for the first time confirmed on North Hemisphere.